ALLERGIC CONTACT DERMATITIS FROM FORMALDEHYDE EXPOSURE. - Maya Lyapina; Angelina Kisselova-Yaneva; Assya Krasteva; Mariana Tzekova-Yaneva; Maria Dencheva-Garova (Peytchinski Publishing, 2012)
Formaldehyde is a ubiquitous chemical agent, a part of our outdoor and indoor working and residential environment. Healthcare workers in difficult occupations are among the most affected by formaldehyde exposure. Formaldehyde is an ingredient of some dental materials. Formaldehyde is well-known mucous membrane irritant and a primary skin sensitizing agent associated with both contact dermatitis (Type IV allergy), and immediate, anaphylactic reactions (Type I allergy). Inhalation exposure to formaldehyde was identified as a potential cause of asthma. Quite a few investigations are available concerning health issues for dental students following formaldehyde exposure. Such studies would be beneficial for early diagnosis of hypersensitivity, adequate prophylactic, risk assessment and management of their work.